In vivo functionalization of biosilica from Thalassiosira weissflogii with a two-photon red emitting fluorescent tag. (5th February 2018) - Vona, Danilo; Leone, Gabriella; Lo Presti, Marco; Ragni, Roberta; Daniel, Jonathan; Blanchard-Desce, Mireille; Farinola, Gianluca M.; Cicco, Stefania R.
ABSTRACT: The chemical decoration of biosilica shells (frustules) from microalgae with several classes of organic molecules is a convenient, scalable biotechnological route to silica nanostructures with applications ranging from photonics to biomedicine. Here we report for the first time the in vivo staining of Thalassiosira weissflogii diatoms with a two photon red emitting triphenylamine-based fluorescent dye bearing a triethoxysilyl functional group (tPhA-Silane). In vivo staining of the cells has been investigated with confocal microscopy and hybrid silica structures comprising the dye embedded into the biosilica have been isolated by proper protocols able to remove the organic protoplasm.